Powering Down the Computing Infrastructure. - Lawton, George (Computer (00189162), 2007)
The article focuses on the issue of power usage by the world's computer servers. Most PC motherboards convert the electricity coming from the power supply into different voltages to meet the needs of the computer components, which creates power use inefficiencies. In 2004 Ecos and Northwest Alliance launched an initiative to give incentives to companies that deploy power supplies with high efficiencies across a range of loads. Manufacturers are also developing new systems to regulate system temperatures without consuming more energy in the process. A chart showing the steadily increasing cost of powering and cooling servers is included.